Digital collaborative consumption and social issues: The clash of taxi and Uber driver in Surabaya and Taipei - Kholifatus Saadah; Shafira Elnanda Yasmine; A. Safril Mubah (Masyarakat, Kebudayaan dan Politik, 2017)
Since the occurrence of application-based taxi, phenomenon and resistance have emerged in metropolitan cities around the world. One of the main issues highlighted is digital collaborative consumption which emerges as the consequences of globalization. As an interpretive case study research, this paper aims to analyze the use of Uber as an alternative to public transportation in Taipei and Surabaya. Authors discuss the issue by comparing the reaction toward the occurrence of Uber and Taipei and Surabaya. Authors apply the theory from Hegre, Gissinger, & Gledtisch (2002) about globalization and social conflict to explain social issues as the consequences of digital collaborative consumption as the new consumption model. According to the theory, globalization creates a deprivation which makes the struggle to access source of capital become more intense. Poverty is the main generator of radical action and violence. Analyzing the phenomena of Uber usage and the resistance from traditional taxi businessmen in Taipei and Surabaya, the authors argue that globalization reflected on digital collaborative consumption could lead to social unrest for parties who cannot adapt to the changes in economic practice. As shown by many cases of app-based rejection taxi in public places such as airport, train station and bus station; the traditionalists show resistance towards globalization and the economic shift of public transportation business model.